At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
1-5i + n = 0 1+5i +m = 0 n= -1+5i m= -1-5i (1-5i -1+5i) (1+5i -1-5i)
1 +5i -1 -5i -5i -25i^2 +5i +25i^2 -1 -5i +1 +5i 5i +25i^2 -5i -25i^2
guess it aint gonna work out like i thought :) gotta head to marketing class now; Ciao :)
\[ f(x) = (x-(1+5i))(x-(1-5i)) \] \[ = x^2 - x(1-5i) -x(1+5i) + (1+5i)(1-5i)\] \[ = x^2 -x +5xi - x - 5xi + 1 -5i + 5i - 25i^2\] \[ = x^2 - 2x + 1 + 25 \] \[ = x^2 - 2x + 26 \] \[ \rightarrow f(1-5i) = 0, f(1+5i) = 0\]
When you are doing this problem: I understand the first equation is just subtracting from x then the secong equation you are distributing... why do you add the additonal (1+5i)(1-5i)??
It's all the same equation. I didn't add the (1+5i)(1-5i). That term is the result of multiplying the last term in each factor.. \[ (a - b)(a - c) = a^2 -ac -ab +bc\] Where b in this case is (1+5i) and c is (1-5i)
Ok..I dont understand. But thank you so much for you help. I have the answer just not sure how I got it... thanks again.
Well wait. Which part don't you understand?
It doesn't do any good to have the answer and not understand how you got it. Otherwise you won't be able to use this tool on more complicated tasks.
Do you agree that \[ (x-a)(x-b) = x^2 - ax -bx +ab \]
Yes I agree. That would be just simply distrubtng....
Right. Do you also agree that if x=a or x=b then the product (x-a)(x-b) would be 0 because one of the factors would be 0?
Did I lose you?
Kinda.. because I dont know where the zero comes from??
\[ If\ x = a, then\ (x-a) = (a-a) = 0 \rightarrow (x-a)(x-b) = 0*(a-b) = 0\]
Thanks for your help.. I dont want to waste anymore of your time...
... You're not wasting my time. Did you understand my last sentence?
\[ \rightarrow \] just means 'therefore'
I wish I did...
Let x = a. Then (x-a) = (a-a). (a-a) = ?
Yes. a - a = 0. No matter what 'a' is.
Ok.. so now that I know that.. what signifigance does that have in my problem?
So what we're saying is that when x = a, (x-a) = 0. If (x-a)=0 then (x-a)(x-b) would be 0*(x-b) which is?
The point of the problem is to find a polynomial that has 2 roots. That means that there are two different values for x at which the polynomial will be 0. We construct such a polynomial by writing an expression which has two factors (x-a)(x-b) Where a and b are the two roots (0's). When x is equal to either a or b, the whole expression will be equal to 0.
Does that make sense?
Thanks for your help. But I really need to go. Im not getting it. But appreciate your help so much...
Give it some thought. And try to follow through what I've written. If you have questions, feel free to come back and ask.